2010
DOI: 10.3189/002214310791968403
|View full text |Cite
|
Sign up to set email alerts
|

The structure, biological activity and biogeochemistry of cryoconite aggregates upon an Arctic valley glacier: Longyearbreen, Svalbard

Abstract: Glacier surfaces support unique microbial food webs dominated by organic and inorganic debris called 'cryoconite'. Observations from Longyearbreen, Spitsbergen, show how these aggregate particles can develop an internal structure following the cementation of mineral grains (mostly quartz and dolomite) by filamentous microorganisms. Measurements of carbon and dissolved O2 show that these microorganisms, mostly cyanobacteria, promote significant rates of photosynthesis (average 17 ?gC g?1 d?1) which assist aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
184
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(205 citation statements)
references
References 30 publications
19
184
2
Order By: Relevance
“…Takeuchi (2002) found C/N mass ratios between 9 and 14 (mostly around 11) for different cryoconites of nine glaciers from the Himalaya, Tibet, and the Arctic. In addition, Hodson et al (2010b) found a C/N mass ratio of 13 ± 1 for cryoconite from Longyearbreen, a valley glacier in Svalbard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takeuchi (2002) found C/N mass ratios between 9 and 14 (mostly around 11) for different cryoconites of nine glaciers from the Himalaya, Tibet, and the Arctic. In addition, Hodson et al (2010b) found a C/N mass ratio of 13 ± 1 for cryoconite from Longyearbreen, a valley glacier in Svalbard.…”
Section: Discussionmentioning
confidence: 99%
“…Takeuchi (2002) found that the amount of dark coloured organic substances, possibly the residue of bacterial decomposition of organic matter, determines the optical characteristics of the cryoconite. In addition, the aggregation of dark particles and organic debris by extracellular polymeric substances affects the light absorbency of the cryoconite (Hodson et al, 2010b). Uetake et al (2010) found that a higher biovolume and differences in species composition account for the darker surface of Russell glacier compared to the Qaanaaq Glacier, both in West Greenland.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dispersed cryoconite can contribute up to half the total cryoconite coverage on Arctic valley glaciers, and may have the potential to be biologically active . Third, there may be significant additional loss of TIN (aq) via microbial denitrification, perhaps by microbes located within the anoxic interior of cryoconite granules (Hodson et al, 2010a).…”
Section: Active Nitrogen Fixation In the Marginal And Glacier Zonesmentioning
confidence: 99%
“…Considering these factors, it is important to identify glacier-wide variability in carbohydrate production, as carbohydrates may control the formation of aggregates upon glaciers and ice sheets (e.g. Hodson et al, 2010;Stibal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%